Modelagem paramétrica para estimativa de custos e quantitativos em redes de distribuição de água - GONZALEZ, Gabriel Souza (2024)
This study proposes a statistical analysis of budgetary data with the aim of facilitating the formulation of parametric estimates in the context of the construction of water supply networks. To achieve this purpose, a database was created consisting of project budgets from the Companhia de Saneamento do Pará (Cosanpa), with the objective of using linear regression to define equations that provide accurate estimates. In the cost analysis, the reference works showed an average variation of 4.37% and 9.47%, both in comparison with the actual budget. In the analysis of parametric quantity models, the average variation for the reference works was 1.22% and 10.31%, respectively.